1989
DOI: 10.1143/jjap.28.l849
|View full text |Cite
|
Sign up to set email alerts
|

New Phases in the Ferroelectric Liquid Crystal MHPOBC Studied by Differential Scanning Calorimetry

Abstract: This paper demonstrates that powerful laser radiation causes changes in the absorbance spectra of epoxy resin, polyethylene and polysulfone. Thin polymer films were located between IR AgBrCl optical fibres and exposed to the radiation of a CO 2 laser. The output of the laser source was varied in the range 0-8.5 W. The absorbance spectra were recorded using a Fourier transform infrared (FTIR) spectrophotometer. It was revealed that characteristic polymer absorbance peaks decay under exposure to the powerful IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…Since 1988 when antiferroelectric liquid crystals (AFLCs) were synthesized for the rst time [1], a lot of experimental [2] and theoretical [3] work has been done to study their dielectric and electrooptic properties. AFLCs have become a very interesting eld of research due to their practical applications in science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1988 when antiferroelectric liquid crystals (AFLCs) were synthesized for the rst time [1], a lot of experimental [2] and theoretical [3] work has been done to study their dielectric and electrooptic properties. AFLCs have become a very interesting eld of research due to their practical applications in science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the SmC * α phase is unique. This phase was already found by DSC measurement in 1989 [1,2], but it took 10 years to clarify the structure by such sophisticated experiments as resonant X-ray diffraction [3] and differential optical reflectivity [4]. It was found that the SmC * α phase has a helical structure like the ferroelectric SmC * phase, but the pitch is very short.…”
Section: Introductionmentioning
confidence: 87%
“…The prototype of the AFLC compound was MHPOBC. It has been found that AFLC materials [2,3] exhibit not only the SmC * and SmC * A phases, but additionally there may appear three other sub-phases, which were much more dicult to be recognized. These sub-phases appear in a phase diagram when the optical purity of the sample increases.…”
Section: Introductionmentioning
confidence: 99%